Internet and distributed computing advancements : theoretical frameworks and practical applications - Abawajy, Jemal; Pathan, Mukaddim; Rahman, Mustafizur; Pathan, Al-Sakib Khan; Deris, Mustafa Mat (IGI Global, USA, 2012)
As software and computer hardware grows in complexity, networks have grown to match. The increasing scale, complexity, heterogeneity, and dynamism of communication networks, resources, and applications has made distributed computing systems brittle, unmanageable, and insecure.